Il soggettivismo postmoderno e la ‘purezza aurorale’ del greco delle origini: Martin Heidegger traduttore di Anassimandro (Atti del Sodalizio Glottologico Milanese, 2014)
The origin of French Postmodernism approach is to be attributed to Martin Heidegger, who, in his translation of Anaximander, investigates the primeval (“auroral”) state of Greek language and thought, identifying these in Ionic and Homer. The great philosopher takes does not take into account the fact that the Ionic compilation of Greek epos is a mere historical accident; being unable to foresee, towards the end of 1948, the imminent decipherment of Myceanaean, he makes philosophical and linguistic origins coincide, and therefore confers to Anaximander’s dicta a lexicon which is unconfirmed by Greek historical tradition, while corresponding exclusively to the theoretical postulates of his book Sein und Zeit. We are thus dealing with a totally unfounded a posteriori projection, bearing little or no respect for the scientific protocol of diachronic linguistics. KEYWORDS: Heidegger, Anaximander, Greek, translation, language origins